2015
DOI: 10.1111/are.12799
|View full text |Cite
|
Sign up to set email alerts
|

Using a fermented mixture of soybean meal and earthworm meal to replace fish meal in the diet of white shrimp,Penaeus vannamei(Boone)

Abstract: An experiment was conducted to evaluate the potential of a Bacillus subtilis E20-fermented mixture (FSFEM) containing soybean meal (SBM) and Eisenia fetida earthworm meal (EM) at a ratio of 4:1 to increase the methionine level in order to satisfy the methionine requirement of white shrimp, Penaeus vannamei in a diet with fish meal (FM) completely replaced by mixtures. B. subtilis E20 fermentation improved the mixture's palatability and utilization based on better growth performance in comparison to shrimp fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Similarly, the rate of fishmeal substitution was 50% by fermented cottonseed meal (Sun et al, ) and 30% by FRSM (Jannathulla, Dayal, Ambasankar, et al, ) in the diet of P. vannamei , which was almost 22% and 42%, respectively, lesser than our results. However, the report of Chiu et al () showed 80% of fishmeal substitution in P. vannamei when FSBM and fermented earthworms were used in combination. The enhanced result of Chiu et al () compared with our present result would be due to the inclusion of earthworm, which would be a valuable nutritional resource after removing coelomic fluid and/or mucus due to fermentation.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the rate of fishmeal substitution was 50% by fermented cottonseed meal (Sun et al, ) and 30% by FRSM (Jannathulla, Dayal, Ambasankar, et al, ) in the diet of P. vannamei , which was almost 22% and 42%, respectively, lesser than our results. However, the report of Chiu et al () showed 80% of fishmeal substitution in P. vannamei when FSBM and fermented earthworms were used in combination. The enhanced result of Chiu et al () compared with our present result would be due to the inclusion of earthworm, which would be a valuable nutritional resource after removing coelomic fluid and/or mucus due to fermentation.…”
Section: Discussionmentioning
confidence: 97%
“… Vitamin premix contained the following mixture (mg/g): para‐aminobenzoic acid, 10; inositol, 100; pyridoxine hydrochloride, 1.5; riboflavin, 0.83; nicotinic acid, 0.27; thiamine hydrochloride, 0.52; retinol acetate, 0.64; menadione, 1.5; DL‐α‐tocopheryl acetate, 10; cyanocobalamine, 0.0074; cholecalciferol, 0.0037; folic acid, 0.08; choline chloride, 153.8; d‐biotin, 0.09; calcium pantothenate, 5.15. All ingredients were diluted with a‐cellulose to 1 g (Chiu et al, ). …”
Section: Pellet Feeds Supplemented With Different Concentrations Of Smentioning
confidence: 99%
“… Mineral premix contained the following mixture (mg/g): K2HPO4, 200; NaH2PO4, 215; Ca(H2PO4) ·H2O, 265; CaCO3, 105; KCl, 28; KI, 0.233; MgSO4 0.7H2O, 100; CuCl2.2H2O, 0.153; AlCl3.6H2O, 0.240; ZnSO4.7H2O, 0.240. All ingredients were diluted with alpha‐cellulose to 1 g (Chiu et al, ). …”
Section: Pellet Feeds Supplemented With Different Concentrations Of Smentioning
confidence: 99%
“…Fermentation is an effective method for processing shrimp food to prolong the duration of preservation and enhance the food's flavour and nutritional value (Frias, Song, Martínez‐Villaluenga, González de Mejia, & Vidal‐Valverde, ; Ross, Morgan, & Hill, ). Some recent studies showed that fermentation also has the capacity to improve nutrition and utilization efficiency (Catalán et al, ; Van Nguyen et al, ; Shiu, Hsieh, et al, ; Shiu, Wong, et al, ), functional properties of SBM (Cheng et al, ; Kim et al, ; Sanjukta & Rai, ; Xie et al, ), and other feed ingredients (Chiu et al, ; Nwokola & Sim, ). To date, several studies reported that a diet of FSBM might also bring health benefits to animals (Liu, Feng, Xu, Lu, & Liu, ; Ding, Zhang, Ye, Du, & Kong, ; Wang, Zhou, He, Xu, Mai, & He, ).…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture, probiotics are known to have benefits, such as improving nutrient absorption and the feed conversion efficiency, thereby enhancing growth performance (Daniels et al, ; Lin, Shiu, Chiu, Huang, & Liu, ; Liu, Chiu, Ho, & Wang, ; Tsai, Chi, & Liu, ; Wang, Hu, Chiu, & Liu, ), enhancing immunity and disease resistance (De et al, ; Lin et al, ; Tsai, Santos, et al, ; Tseng et al, ; Wang et al, ), and excluding undesirable forms of bacteria in the gut (Huynh, Hu, Chiu, Truong, & Liu, ; Md Zoqratt, Eng, Thai, Austin, & Gan, ). In addition to the above‐mentioned benefits, probiotics are used to improve the nutritional value and utilization of plant ingredients through fermentation (Chiu et al, ; Van Nguyen, Hoang, Van Khanh, Duy Hai, & Hung, ; Shiu, Hsieh, Guei, Chiu, & Liu, ; Shiu, Wong, Guei, Shin, & Liu, ). Furthermore, some studies showed that fermented soybean meal (FSBM) contains biologically active peptides that exert physiological effects on microbes in the gut (Erdmann, Cheung, & Schröder, ), including antimicrobial activity (Kim, Kim, Ko, Lee, Ha, Song, Park, Kwon, Bae, ; Sanjukta & Rai, ; Cheng, Lin, Shiu, Tyan, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%